EFEKTIVITAS STRATEGI KOMUNIKASI UNIT PENGUMPUL ZAKAT (UPZ) DALAM MENINGKATKAN KUALITAS PELAYANAN DAN PENGUMPULAN ZAKAT (Studi Kasus UPZ Masjid Jami’ Jabal Nur, Kota Samarinda): Strategi Komunikasi - Pratama, Aldo; Mulyadi, Rudi; Masahengke, Fredy; Royanti, Royanti; Wahdiansyah, Wahdiansyah (Universitas Nahdlatul Ulama Kalimantan Timur, 2025)
This study examines the effectiveness of communication strategies implemented by the Zakat Collection Unit (UPZ) at the Jami’ Jabal Nur Mosque in enhancing service quality and increasing zakat collection. A qualitative descriptive design was employed, with data collected through in-depth interviews, participant observations, and document analysis. Findings indicate that the UPZ employs a multi-pronged communication strategy, incorporating interpersonal communication, the use of social media platforms, religious sermons, and a zakat pickup service. Several facilitating factors were identified, including the involvement of local community leaders, support from the mosque council, and transparent financial management. Conversely, the implementation process is hindered by constraints such as limited human resources and low public awareness regarding zakat obligations. The study concludes that the UPZ’s communication strategies have been effective in building community trust and enhancing participation in zakat distribution. These findings contribute to the growing body of literature on faith-based organizational communication and offer a practical model for other mosque-based zakat management institutions seeking to improve their outreach and service delivery.